2017
DOI: 10.1103/physrevb.95.155433
|View full text |Cite
|
Sign up to set email alerts
|

Understanding magnetic focusing in graphene pn junctions through quantum modeling

Abstract: We present a quantum model which provides enhanced understanding of recent transverse magnetic focusing experiments on graphene p-n junctions. Spatially resolved flow maps of local particle current density show quantum interference and p-n junction filtering effects, which are crucial to explaining the device operation. The Landauer-Büttiker formula is used alongside dephasing edge contacts to give exceptional agreement between simulated nonlocal resistance and the recent experiment by Chen et al. [Science 353… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 47 publications
(86 reference statements)
0
11
0
Order By: Relevance
“…In the ballistic limit, reflecting walls may add a non-trivial background to the conductance signal of interest, which may become more complex in coherent conditions (see, for example, ref. 53 , Fig. 4 ), analogous to reverberation and standing acoustic waves in a poorly dampened room.…”
Section: Resultsmentioning
confidence: 97%
“…In the ballistic limit, reflecting walls may add a non-trivial background to the conductance signal of interest, which may become more complex in coherent conditions (see, for example, ref. 53 , Fig. 4 ), analogous to reverberation and standing acoustic waves in a poorly dampened room.…”
Section: Resultsmentioning
confidence: 97%
“…This behavior is the analog of a Veselago lens 18 that was realized earlier in photonic crystals 19,20 and metamaterials [21][22][23] . These findings led to profound theoretical investigations of electron focusing in SLG [24][25][26] as well as in AA- 27 and AB-BLG 28 where a valley selective electronic Veselago lens was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The vortices cannot be understood by examining individual single-particle trajectories, but rather appear as collective phenomena of all the particles as a whole, in currents resulting from a vector sum over all the trajectories. While TMF has seen extensive numerical study 41 46 , current vortices have not been reported till this work. A probable reason lies in the observation that current computation may be dominated by shot noise in TMF simulations performed using particle schemes 44 , 45 , a limitation not suffered by the present high-resolution kinetic scheme.…”
Section: Discussionmentioning
confidence: 91%
“…A probable reason lies in the observation that current computation may be dominated by shot noise in TMF simulations performed using particle schemes 44 , 45 , a limitation not suffered by the present high-resolution kinetic scheme. It would be interesting to check if vortices persist in the coherent transport regime 43 , 46 .…”
Section: Discussionmentioning
confidence: 99%